Gloeocantharellus andasibensis sp. nov. (Gomphaceae) from Madagascar - Ralaiveloarisoa, Anna Berthe; Liimatainen, Kare; Ralimanana, Helene; Jeannoda, Vololoniaina; Cable, Stuart; Niskanen, Tuula (Phytotaxa, 2021)
Gloeocantharellus andasibensis sp. nov. is recognized by orange-red basidiomata with a convex to plane, innately fibrillose and viscid pileus, ellipsoid to amygdaliform, small, verrucose basidiospores, and a distinct nrITS sequence. This is the first record of the genus from Madagascar. To improve the understanding of the nomenclature of the genus, the type specimen of G. okapaensis and specimens of G. lateritius and G. corneri accessioned in the fungarium of the Royal Botanic Gardens, Kew were also sequenced.